Seed size evolution and biogeography of Plukenetia (Euphorbiaceae), a pantropical genus with traditionally cultivated oilseed species - Cardinal-McTeague, Warren M; Wurdack, Kenneth J; Sigel, Erin M; Gillespie, Lynn J (Université d'Ottawa | University of Ottawa, 2019)
Abstract Background Plukenetia is a small pantropical genus of lianas and vines with variably sized edible oil-rich seeds that presents an ideal system to investigate neotropical and pantropical diversification patterns and seed size evolution. We assessed the biogeography and seed evolution of Plukenetia through phylogenetic analyses of a 5069 character molecular dataset comprising five nuclear and two plastid markers for 86 terminals in subtribe Plukenetiinae (representing 20 of ~ 23 Plukenetia species). Two nuclear genes, KEA1 and TEB, were used for phylogenetic reconstruction for the first time. Our goals were: (1) produce a robust, time-dependent evolutionary framework for Plukenetia using BEAST; (2) reconstruct its biogeographical history with ancestral range estimation in BioGeoBEARS; (3) define seed size categories; (4) identify patterns of seed size evolution using ancestral state estimation; and (5) conduct regression analyses with putative drivers of seed size using the threshold model. Results Plukenetia was resolved into two major groups, which we refer to as the pinnately- and palmately-veined clades. Our analyses suggest Plukenetia originated in the Amazon or Atlantic Forest of Brazil during the Oligocene (28.7 Mya) and migrated/dispersed between those regions and Central America/Mexico throughout the Miocene. Trans-oceanic dispersals explain the pantropical distribution of Plukenetia, including from the Amazon to Africa in the Early Miocene (17.4 Mya), followed by Africa to Madagascar and Africa to Southeast Asia in the Late Miocene (9.4 Mya) and Pliocene (4.5 Mya), respectively. We infer a single origin of large seeds in the ancestor of Plukenetia. Seed size fits a Brownian motion model of trait evolution and is moderately to strongly associated with plant size, fruit type/dispersal syndrome, and seedling ecology. Biome shifts were not drivers of seed size, although there was a weak association with a transition to fire prone semi-arid savannas. Conclusions The major relationships among the species of Plukenetia are now well-resolved. Our biogeographical analyses support growing evidence that many pantropical distributions developed by periodic trans-oceanic dispersals throughout the Miocene and Pliocene. Selection on a combination of traits contributed to seed size variation, while movement between forest edge/light gap and canopy niches likely contributed to the seed size extremes in Plukenetia.